Malignant Transformation of a Mature Cystic Ovarian Teratoma into Thyroid Carcinoma, Mucinous Adenocarcinoma, and Strumal Carcinoid: A Case Report and Literature Review - Hilary D. Hinshaw; Ashlee L. Smith; Mohamed Mokhtar Desouki; Alexander B. Olawaiye (Hindawi Limited, 2012)
Malignant transformation of a mature cystic teratoma (MCT) is an infrequent, often asymptomatic event. We report the first example of a struma ovarii with a focus of follicular variant of papillary thyroid carcinoma (a), mucinous adenocarcinoma (b), and strumal carcinoid tumor (c)-all three arising in one mature cystic teratoma of the ovary. From our reviews, we found limited data to guide management when these malignant foci occur within an MCT. Consideration should be given to thyroidectomy followed by total-body scanning and serum studies for foci of thyroid carcinoma and adjuvant therapy with thyroidectomy and radioablation if residual disease is identified (a). Additionally, extrapolating from data for mucinous adenocarcinomas, consideration could be given to adjuvant chemotherapy after appropriate staging (b). Strumal carcinoid tumors should be treated as tumors of low malignant potential. Observation is appropriate if after complete staging, no invasive implants are noted (c).